Digital Economy Model in Vietnam - Thi Viet Duc, Dang (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4345, 2022)
Although there is a strong consensus on the need to digitize the economy, countries face challenges of allocating limited resources. Therefore, each country needs to identify a focus area for the development of the digital economy and align its limited resources strategically on building related infrastructure and capacity. The objective of the article is to identify the focus of digital economy development for Vietnam. The article bases on the digital economy development framework proposed by Huawei and Arthur D Little to analyze the situation of Vietnam, determining the current digital economy archetype and the target archetype in the future for the country. The article also proposes overall policy-oriented solutions for Vietnam to continue to efficiently exploit the current digital economy archetype and gradually shift to an alternative archetype in the future.